Restaurant Project - Mohammad Assaf (My University, 2010)
Nowadays all the organizations in all the word, goes  to use the technology in their daily processes, in order to manage and simply maintain their works and process, this make  the organization more dynamic and has the ability to response to the change.        Because of the network, and its ability to connect people together, and it's application such as internet, this make it easier to deal with different transactions remotely and dynamically such as, EBanking, ECommerce, EShopping that is used over the existence of the internet.

Nowadays all the organizations in all the word, goes  to use the technology in their daily processes, in order to manage and simply maintain their works and process, this make  the organization more dynamic and has the ability to response to the change.        Because of the network, and its ability to connect people together, and it's application such as internet, this make it easier to deal with different transactions remotely and dynamically such as, EBanking, ECommerce, EShopping that is used over the existence of the internet.